Is There any Differences of Job Stress Among Correctional Officers Based on Gender in Java? - Unika Prihatsanti; Ika Zenita Ratnaningsih; Anggun Resdasari Prasetyo (Journal of Educational, Health and Community Psychology, 2017)
AbstractThe purpose of this study is to investigate the differences of job stress based on gender among correctional officers in three prisons in Java Indonesia. This study was a quantitative survey study focused on the comparison between male and female. The data were collected from 95 correctional officers from Bandung and Semarang prisons. The analysis of variance test (ANOVA) was used to test the study hypotheses. The results show that gender variable has influences on job stress, in which female correctional officers have higher job stress level than male correctional officers.Â Keywords: gender, job stress, correctional officers